The Competitiveness in the Banking Industry in Palestine - Ayyash, Issam; Abdel Jawad, Yousef Abdel Latif (International Journal of Economics and Financial Issues, 2020)
The study measures the degree of competition in the banking industry in Palestine for the period from 2006 to 2010. It begins by measuring Lerner index, and then estimates the determinants of market power by regressing Lerner index on returns of assets and lending preferences. It uses data on 18 working banks in Palestine; the data is secondary, time-series and cross-sectional obtained by the Association of Banks in Palestine. The study establishes the log-log model for estimation and tests the variables according to the Ordinary Least Square method. The study concludes that the banking industry in Palestine is controlled by a few players, the assets concentration ratio is about 75%. About 72% of the working banks can raise the price above the marginal cost, and then able to earn profits. Keywords: Competition, Market power, Lerner index, Banking industry. JEL Classifications: B41, C32, L11, P34 DOI: https://doi.org/10.32479/ijefi.9008